Efeito anti-proliferativo de curcumina associada á nanopartículas magnéticas funcionalizadas com bicamada de ácido láurico sobre células de melanoma humano skmel 37 - Souza, Fernanda França de (2011)
Curcumin has emerged as a great promise for cancer treatment and chemoprophylaxis with curcumin, but its low solubility in water is minimal systemic bioavailability. Attempts were made to improve its solubility in aqueous solutions by incorporating curcumin in liposomes or micelles, but these systems have low stability. In addition, magnetic nanoparticles have been used as promising drug delivery systems because they can be functionalized to become water soluble and biocompatible. Studies with curcumin incorporated into the magnetic nanoparticles are still scarce. This study aims to evaluate the antiproliferative effect of curcumin combined with magnetic nanoparticles functionalized bilayer of lauric acid in human melanoma cell line SKMEL 37. Human melanoma cells were treated at different concentrations and cytotoxicity was evaluated by MTT assay. The cell morphology was evaluated by light microscopy and fluorescence. Our studies have shown that curcumin has incorporated into nanoparticles cytotoxic effect at concentrations above 40,8 μg/ml or 111 μM. Since free curcumin caused significant death at concentrations above 11.5 μM. We also observed morphological changes typical of apoptosis such as chromatin condensation, nuclear fragmentation and bleb formation. These findings show us that both their cytotoxic activity, as both the magnetic properties and its solubility in water make this new formulation with a curcumin compound interest for therapeutic use.